Development and preliminary validation of an automatic digital analysis system for animal fibre analysis - Quispe, M. D. (2017)
New equipment was designed and developed to evaluate the physical characteristics of animal fibres, based on an automatic digital analysis system (ADAS) that allows the capture of a series of real-time images. In the development of the mechanical component, a design tool was used that allows visualization, simulation, and documentation of the product.